Integrating Al-Kafaf and Al-Kifayah in Malaysian Income Assessment: An Islamic Economic Perspective on Holistic Well-being - Abdul Muzil Abd Rahim; Muhammad Nazir Alias; Anwar Fakhri Omar; Muhamad Mu'izz Abdullah; Zuliza Mohd Kusrin; Mohd Al Adib Samuri; Nik Abdul Rahim Nik Abdul Ghani; Sheila Fakhria (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This study critiques Malaysia’s traditional income-based classifications (B40, M40, T20) for failing to capture multidimensional poverty amid rising living costs and regional disparities. It introduces Islamic economic concepts—al-kafaf (minimum subsistence threshold) and al-kifayah (broader sufficiency standard)—as alternative frameworks for assessing household income within modern B20, M50, and T30 classifications. Using qualitative methodology combining case studies with conceptual-comparative analysis, the research examines the limitations of conventional income metrics. Findings show that traditional classifications effectively show income gaps but inadequately reflect actual living costs and regional economic variations. Al-kafaf establishes a basic survival baseline, while al-kifayah offers a holistic measure incorporating education access, healthcare, and quality of life. This integration improves welfare and zakat targeting while contributing to more equitable policymaking frameworks. The study advances Islamic economic theory by proposing a holistic approach to measuring economic well-being that better aligns with current socioeconomic realities. The primary academic contribution of this study lies in the development of a more contextual and multidimensional Islamic economic framework for evaluating household well-being. Furthermore, the research expands the horizons of Islamic economic theory by offering a normative-practical approach to income assessment while also providing a new conceptual foundation for policymakers to design income classifications that are more adaptive to contemporary socioeconomic realities